Mengembangkan Human Resource Management yang Strategis untuk Menunjang Daya Saing Organisasi: Perspektif Manajemen Kinerja (Performance Management) di Bank Syariah - Ahmad Azmy (Bina Nusantara University, 2015)
This article discusses performance management in sharia banks related to human resources. The method used is descriptive in providing a comprehensive explanation based on factual data. Performance management in sharia banks should be applied based on the characteristics of human resources by sharia. The characteristics of the human resources required by sharia banks are different from conventional banks. Human resources in sharia banks should have different performance indicators to conventional banks. Performance indicators serve as a guide in the process of implementing sustainability performance as an effort of sharia banking in the banking industry in Indonesia.